Attitude Factors Affecting Teachers’ Use of Short Stories in the Teaching of Kiswahili Grammar in Secondary Schools in Nandi North Sub-County, Kenya - Lihanda, Milton Kigaro; Agufana, Peace Byrne (European Scientific Journal, ESJ, 2017)
This study investigated attitude factors affecting teachers’ use of short stories in the teaching of Kiswahili grammar in Secondary Schools in Nandi North Sub County, Kenya. The design for this study was descriptive survey. The total target study population was 50 Kiswahili language teachers in Secondary Schools in Nandi North Sub-County, in Kenya. Sampling was done through stratified and simple random sampling techniques to arrive at 50% of the target population. A total of 15 Kiswahili language teachers (n=15) respondents participated in the study. Data was collected through the use of questionnaires for teachers. The data was analyzed using descriptive statistical methods such as frequencies, and percentages. The study found out that very few teachers used short stories in teaching Kiswahili grammar. The research found out that teachers’ attitude towards use of short stories in teaching and learning Kiswahili grammar was positive. Based on the findings, the study recommends that teachers should use short for effective Kiswahili grammar teaching.